THE ROLE OF PEDAGOGICAL SCIENCE AND METHODS OF USING METHODS IN TEACHING GENERAL SCIENCES - Akhmedov Islombek; Umarov Isroil; B.Sharopov (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: In this article, it is shown that the branches of pedagogic science, the method of science studying the laws of teaching subjects, at the same time, pedagogic science cannot develop in isolation from other disciplines. As the object of pedagogy in the field of education is the growing young generation, it is shown that pedagogy greatly helps in mastering students.